AB0742 Minimally invasive ultrasound guided synovial biopsy as a clinical diagnostic tool. (23rd January 2014) - Ng, N.; Di Cicco, M.; Humby, F.; Deidda, S.; Pyne, D.; Kidd, B.; Sutcliffe, N.; Jawad, A.; Breston, C.; Pitzalis, C.; Kelly, S.
Abstract : Background: Diagnostic synovial biopsies (Bx) are key investigations which traditionally involves an invasive orthopaedic arthroscopic procedure. However, in our department, all our diagnostic synovial biopsies are performed by rheumatologists using a minimally invasive ultrasound (US) guided technique that has been shown to be safe and well tolerated 1 . Objectives: This audit was undertaken to review our activities, outcome (tissue diagnosis), tissue quality and safety of the procedure. Methods: 26 patients underwent an outpatient diagnostic synovial biopsy from May 2011 to October 2012. Data was collected from casenotes and online care record system. Biopsies were performed in sterile aseptic conditions. After local anaesthesia, a 16G core Bx needle is placed within the joint capsule under US visualisation and is guided to the appropriate site for sampling. Tissue samples were placed in formalin for histology (Histo) analysis, but kept fresh for microbiology and crystal analysis. Results: Activity: Joints Biopsied - knees (n=8, 31%), wrists (n=6, 23%) flexor tendon sheath (n=2, 8%), MCPJs (n=2, 8%), MTPJs (n=2, 8%), ankles (n=2, 8%), shoulder, elbow, PIPJ and DIPJ(n= 1 each, 4%). The commonest indication was to exclude an infective arthritis (n=18, 70%), followed by requests to aid diagnosis of crystal arthritis (n=4, 15%) and sarcoidosis (n=4, 15%). Timing of Bx: 78% of all Bx were performed within 5 days of request, of which 54% within 3 days and 31% within 1 day. Tissue quality: All samples harvested were of good quality for laboratory processing bar 1 biopsy with insufficient tissue for histopathological but enough for microbiology. Safety: A majority of patients (92%) had an uncomplicated Bx. 2 patients (8%) described arthralgia and swelling at Bx site 48 hours post procedure. No evidence of haemarthrosis or infection was found and pain settled with simple analgesia after 2 days. Outcome: 4 cases of TB arthritis were diagnosed (22%, 4/18). 2 patients had granulomas seen on histo, 2 other patients had positive AFB smear. Of those suspected of sarcoidosis, 1 case was positive for granuloma on the flexor tendon sheath, with negative IGRA suggesting sarcoid tenosynovitis. No crystals were seen in any of the samples harvested for cases suspected of crystal arthritis. Follow up : Patients who have received an US guided synovial biopsy with a negative result were diagnosed with an undifferentiated inflammatory arthritis and received immunosuppressive treatment. To date (mean follow up of 13 months), none of these patients were subsequently diagnosed with an infected arthritis suggesting tissue samples for microbial analysis were adequate for accurate analysis. Conclusions: Minimally invasive US guided synovial biopsy is a valuable clinical diagnostic tool that enables safe, quick and adequate tissue sampling for microbiology and histopathological analysis. We would suggest for this technique to be introduced in other rheumatology centres as a clinical diagnostic tool. Larger number of biopsies will need to be looked at to better determine the negative predictive value of this tool in the context of suspected septic arthritis. References: Kelly S, et al. Ultrasound guided synovial biopsies: safety, tolerability and tissue quality. Rheumatology 2012; 51(suppl 3): iii52-iii92 Disclosure of Interest: None Declared